A Theory of Procedurally Rational Choice: Optimization without Evaluation - Stefano Ficco; Vladimir Karamychev; Peran van Reeven (Tinbergen Institute, 2006)
This paper analyses the behavior of an individual who wants to maximize his utility function, but he is not able to evaluate it. There are many ways to choose a single alternative from a given set. We show that a unique utility maximizing procedure exists. Choices induced by this optimal procedure are always transitive but generally violate the Weak Axiom. In other words, utility maximizing individuals who are unable to evaluate their objective functions fail to exhibit rational revealed preferences.
Keywords: D01; D81; 330; Bounded rationality; optimal selection procedure; procedural rationality